Depolarization of microwave/millimeter wave in sand and dust storms - Srivastava S.K.; Vishwakarma B.R. (My University, 2025)
A theoretical investigation has been carried out to evaluate the effect of depolarization on the propagation of microwave/millimeter wave in sand and dust storms. The storm is considered to have three main constituents i.e, sand, silt and clay. An equation has been developed for depolarization in which the concept of scattering by dipole as well es back scattering has been utilized for this purpose. It has been found that the depolarization end loss due to depolarization caused by dust particles depend directly on orientation of incident beam, frequency and particle density. The results obtained are in good agreement with experimental results reported earlier. This verifies the accuracy of theory developed.